Redesain Stadion Joyokusumo Pati dengan Konsep Green Architecture - Samaran, Amor, Wisnu Setiawan, ST., M.Arch., PhD (2017)
Joyokusumo Stadium is a sports complex which has a land area of 6,8 hectares located in Pati, Pati regency, which consists of sports as basketball, volleyball, tennis, sepak takraw, rock climbing, archery, and Sebak ball, in addition to the new sports complex, Joyokusumo stadium complex also has a pavilion that serves as a container dealer artistic activity in Pati regency. Stadium complex function Joyokusumo Pati was not optimal as container dealer sport activities, because the facility does not meet the standards, many are unfit for use and terbengakai, especially football field and facilities penunjangnya.Dari these problems comes the completion of the design to overcome these problems, that is to redesign stadium complex by focusing on one sport, soccer, so automatic other sports will be deleted. Responding to the issue of global warming in this era makes architects should be memperhaikan the effects of a development. The stadium redesign plan will use the Standard District Stadium with a capacity of 14.090 spectators, the general audience of 12,000, 1,990 VIP audience, and an audience of 100 persons with disability. Standard field size was increased to international standards according FIFA standards. The emphasis of the concept of green architecture in this building lies in the use of environmentally friendly building materials, such as paving block, ACP, and ETFE.